2006
DOI: 10.1016/j.margeo.2006.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Shoreface migrations at the shelf edge and sea-level changes around the Last Glacial Maximum (Gulf of Lions, NW Mediterranean)

Abstract: The Bourcart-Hérault canyon interfluve in the Gulf of Lions (NW Mediterranean) was the site of very high sedimentation (up to 2.5 m/kyr) around the Last Glacial Maximum, due to the vicinity of major fluvial systems that fed the shelf edge. Shoreface deposits and offshore muds deposited during each glacial/interglacial 100 kyr-cycle, created a repeated motif with highangle and low-angle clinoforms on seismic profiles. New detailed morphological, sedimentological and paleo-environmental data, constrained by 14 C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 55 publications
(71 reference statements)
5
81
0
3
Order By: Relevance
“…The progradation or retrogradation of the deltaic system is, in turn, driven by the interplay of eustatic sea level change, tectonic movement of the continental margin, and variations in sediment supply by rivers that continuously change the balance between the generation/reduction of accommodation space and the sediment filling of this space. However, extensive seismic studies have shown that eustatic changes played the dominant role in the Gulf of Lions (Tesson et al, 1990;Posamentier et al, 1992;Gensous and Tesson, 2003;Rabineau et al, 2005Rabineau et al, , 2006Jouet et al, 2006;Berne et al, 2007;Bassetti et al, 2008), because the long term subsidence typical of a passive continental margin acted in a longer time scale than the climatic cycles studied here and the Gulf of Lions is distant from the major glacial ice sheets. In addition, sediment or water loading only amplifies the effect of global eustatic changes .…”
Section: Constraints On Condensed Layer Formation In the Gulf Of Lionmentioning
confidence: 75%
See 1 more Smart Citation
“…The progradation or retrogradation of the deltaic system is, in turn, driven by the interplay of eustatic sea level change, tectonic movement of the continental margin, and variations in sediment supply by rivers that continuously change the balance between the generation/reduction of accommodation space and the sediment filling of this space. However, extensive seismic studies have shown that eustatic changes played the dominant role in the Gulf of Lions (Tesson et al, 1990;Posamentier et al, 1992;Gensous and Tesson, 2003;Rabineau et al, 2005Rabineau et al, , 2006Jouet et al, 2006;Berne et al, 2007;Bassetti et al, 2008), because the long term subsidence typical of a passive continental margin acted in a longer time scale than the climatic cycles studied here and the Gulf of Lions is distant from the major glacial ice sheets. In addition, sediment or water loading only amplifies the effect of global eustatic changes .…”
Section: Constraints On Condensed Layer Formation In the Gulf Of Lionmentioning
confidence: 75%
“…Over the last decades several seismic investigations and dated sediment cores allowed to reconstruct the general architecture and stratigraphy of the Late Pleistocene deposits of the Gulf of Lions continental shelf (Tesson et al, 1990(Tesson et al, , 1993(Tesson et al, , 2000Berné et al, 1998;Rabineau et al, 1998Rabineau et al, , 2005Rabineau et al, , 2006Jouet et al, 2006;Bassetti et al, 2008). Those authors documented the superposition of various seismic sequences separated by major discontinuities formed in response to eustatic sea level changes.…”
Section: Gulf Of Lions Continental Marginmentioning
confidence: 99%
“…5b). In the Gulf of Lion, the LGM was characterized by the occurrence of cold and arid episodes (Heinrich events) (Jouet et al, 2006;Beaudouin et al, 2007). Between 20 ka and 17 ka, the sea level was low, and marine sediments in the core were characterized by the proximity of the shoreline and the river mouth at that time and by a significant terrestrial input ( Fig.…”
Section: Gulf Of Lionmentioning
confidence: 99%
“…Outer shelf Quaternary sequences are characterized on seismic reflection profiles by alternating steep and low angle clinoforms that correspond, respectively, to high energy (sand) and low energy (silt) sediments formed during glacial and interglacial cycles (Aloïsi 1986;Bassetti et al 2006;Berné et al 1999Berné et al , 2004Jouet et al 2006;Rabineau et al 2005;Tesson et al 2000). Such outer shelf clinoforms have been attributed to sandy shoreface and muddy offshore deposits, respectively (Berné and Gorini 2005), and related to 100 kyr glacio-eustatic cycles (Rabineau et al 2005).…”
Section: Geological Settingmentioning
confidence: 99%